Prediction of Test Anxiety Based on Difficulties in Emotion Regulation in High School Students in Tehran - Amin Rafiepoor; saeid Shafaqati; Ali Abedini; Tayebeh Jafari (پژوهش در نظام‌های آموزشی, 2019)
Abstract Test anxiety is a disorder that reduces the performance of students. The purpose of this study was to investigate the prediction of test anxiety based on the difficulty dimensions of emotion regulation in high school students in Tehran. The statistical population of the present study was the first high school students of Tehran in the year 1397. 226 of them (132 girls and 94 boys) were selected through multi-stage cluster sampling and participated in this study. Data gathering tools included Spielberger Anxiety Scale (1980) and Difficulty Emotion Regulation Scale (2004). Pearson correlation analysis and Multiple Regression were used to analyze the data. The results of correlation test showed that dimensions of difficulty in emotion regulation were positively correlated with test anxiety. The results of multivariate regression analysis indicated that the difficulty dimensions of emotion regulation play a significant role in explaining the variance of students' test anxiety. Therefore, it is necessary to direct psychological interventions to improve emotional regulation in relation to reducing test anxiety in students .